How psychological needs motivate family firm identifications and identifiers: A framework and future research agenda. Issue 3 (September 2019) - Elsbach, Kimberly D.; Pieper, Torsten M.
Abstract: We develop a framework suggesting how psychological needs may motivate individual identifications with, and identifiers of, family businesses. Grounded in extant research, our framework describes how six types of psychological needs (i.e., needs for self-esteem, continuity, distinctiveness, meaning, efficacy/control, and belonging) can both: (1) motivate individuals to identify with family firms that are defined by specific characteristics, and (2) motivate family firm identifiers to promote specific characteristics as defining their firms. Interestingly, our framework indicates that the characteristic that most commonly motivates family firm identifications and identifiers (by satisfying a number of psychological needs) is not "positive image" (as predicted by theories of social identification), but "shared values". Further, our framework suggests that some family firm characteristics (e.g., "family firm image") may both motivate and demotivate identifications and identifiers by simultaneously satisfying some psychological needs (e.g., needs for distinctiveness), while preventing the satisfaction of other needs (e.g., needs for efficacy). Based on our framework, we outline an agenda for future research that may extend our understanding of the role of psychological needs in family firm identification.